Campus sewage treatment system based on program logic control technology - Jiang Jing; Zhang Xuesong (2012 24th Chinese Control and Decision Conference (CCDC), 2012)
Sewage from our campus was needed to treat urgently due the affect of sewage on the environment becoming more and more seriously. This paper proposes a method of Sequencing Batch Reactor Activated Sludge Process to meet the needs of campus. Therefore, the method is so complicated that only automatic control part was realized. Strengths of Sequencing Batch Reactor Activated Sludge Process were played. PLC controller from Mitsubishi FX2N Series was used in the automatic control system of sewage treatment with stable operation, low cost, good effect and so on.